Analisis Kompetensi Kepala Sekolah (Stusi Kasus Di SD Negeri 1 Dan SD Negeri 2 Kec. Rawas Ulu) - Danim, Sudarwan; Febrianti (Manajer Pendididikan, 2023)
The purpose of this study was to describe the managerial competence, supervision competence and entrepreneurial competence of school principals to describe the leadership role of the principal in public elementary school 2, Rawas Ulu sub-district. This research use desciptive qualitative approach. The data sources used in this study were school principals, deputy principals and teachers. Data analysis was carried out through the stages of data reduction, data presentation, verification and drawing conclusions. The results of the study show (a) the implementation of managerial competence is carried out by compiling an annual program, utilizing teachers and staff, maximizing the optimal use of infrastructure facilities, (b) the implementation of supervision competence is carried out by compiling a supervision program, forming a school supervision team, supervising class visits, conducting coaching individually and in groups to teachers in making lesson plans. (c) the implementation of entrepreneurial competence is carried out by fostering school canteens, conducting partnerships with health centers, local community leaders and fostering students with various life skills.